Upper limb disorders in anaesthetists – a survey of Association of Anaesthetists members. (12th October 2018) - Leifer, S.; Choi, S. W.; Asanati, K.; Yentis, S. M.
Summary: Upper limb disorders (affecting the hand, arm and neck) are common. The nature of anaesthetists' work poses a potential extra risk from poor posture that may contribute to the development of upper limb disorders in this professional group. However, to date, the problem has received scant attention in the literature. Following a 2 to 3‐month period of publicity via newsletter, email and social media, all 10, 231 electronically accessible members of the Association of Anaesthetists were invited by email to complete an online survey that was administered by a third‐party company. A total of 3884 usable responses were received (38%). Analysis of possible risk factors found a significant association between upper limb disorders and years since starting anaesthetic training, having children (irrespective of respondents' sex or the number of children) and right‐handedness. Years of practice and having children are less modifiable identified risk factors. However, right‐handedness may be linked to the ergonomic design of the environment/equipment used within this specialty and may thus be a potentially modifiable risk factor worthy of further investigation.